Faktor-Faktor yang Mempengaruhi Keputusan Pedagang Pasar dan Kaki Lima Menabung di BPRS Mitra Mentari Sejahtera Ponorogo - Yahya Faizal Ajibi; Muhtadin Amri (STEI Kanjeng Sepuh Gresik Jawa Timur, 2022)
Abstract: The purpose of this study was to examine and analyze the influence of cultural, social, personal and psychological factors on the decisions of market traders and street vendors to save at BPRS Mitra Mentari Sejahtera Ponorogo. This study uses quantitative methods. Analysis of the data using multiple linear regression. The sampling technique in this study used the incidental sampling method. Data collection techniques using a questionnaire. Respondents in this study were market traders and street vendors. Based on the results of the research conducted, it can be concluded that: cultural factors have a significant effect on the decisions of market traders and street vendors to save at BPRS Mitra Mentari Sejahtera Ponorogo with a significance level of 0.001 <0.05. Social factors significantly influence the decisions of market traders and street vendors to save at BPRS Mitra Mentari Sejahtera Ponorogo with a significance level of 0.034 <0.05. Personal factors have no significant effect on the decisions of market traders and street vendors to save at BPRS Mitra Mentari Sejahtera Ponorogo with a significance level of 0.152 > 0.05. Psychological factors have no significant effect on the decisions of market traders and street vendors to save at BPRS Mitra Mentari Sejahtera Ponorogo with a significance level of 0.677 > 0.05. And simultaneously (together) cultural, social, personal and psychological factors have a significant effect on the decisions of market traders and street vendors to save at BPRS Mitra Mentari Sejahtera Ponorogo with a significance level of 0.000 <0.05.